Financial Management in Encouraging Digitalization of MSME Businesses - Sunaryo Sunaryo; Muchriana Muchran (International Journal of Economic Research and Financial Accounting, 2025)
Digital transformation is inevitable in the modern business landscape, including for Micro, Small, and Medium Enterprises (MSMEs). However, the adoption of digital technology by MSMEs in Indonesia is still relatively low; the APJII report (2023) shows that only around 34.6% of MSMEs fully utilize digital platforms. In fact, digitalization has been proven to increase operational efficiency, expand markets, and improve the quality of customer service. One important factor that is often overlooked is managerial ability, especially in financial management. Many MSMEs still record their finances manually, or even do not do it at all, making it difficult to make data-based decisions, access funding, or invest in technology. This shows that digitalization requires not only technological readiness, but also good financial management capacity. This study uses a descriptive quantitative approach with a survey method as the main data collection technique. The research population is MSME actors in urban and semi-urban areas that have been operating for at least two years. Sampling was conducted using the purposive sampling method, with the main criteria: (1) MSMEs that have financial bookkeeping activities, and (2) have or are using at least one digital application in business operations. Primary data were collected through a 1–5 Likert scale questionnaire measuring financial management variables (planning, recording, monitoring, and evaluation) and business digitalization variables (use of technology, process efficiency, and expansion of market access). Data were analyzed using descriptive statistics and multiple linear regression. The results of the study showed that good financial management practices contributed significantly to the level of MSME digitalization. MSMEs with a neat financial recording and planning system tend to be more financially ready to adopt digital technology. This finding is in line with the study of Setyawati et al. cite_start which states that the success of adopting digital technology is also determined by internal readiness, including financial governance.